Association Between Non-Dipping and Fragmented QRS Complexes in Prehypertensive Patients - Eyuboglu,Mehmet (2019)
Abstract Background: Fragmented QRS (fQRS) is a sign of adverse cardiovascular events in various cardiovascular diseases. It is also associated with increased blood pressure and non-dipping in hypertensive patients. However, no study has investigated the importance of fQRS in prehypertensive patients. Objectives: The aim of our study is to investigate the relationship between fQRS and non-dipper status in prehypertensive patients. Methods: Two hundred and sixteen eligible, newly diagnosed prehypertensive patients who underwent 24-hour ambulatory blood pressure monitoring (ABPM) for further evaluation of blood pressure between June 2015 and July 2016 were included into the study. Patients were divided into three groups according to ABPM results: normotensives, dipper prehypertensives, and non-dipper prehypertensives. Groups were compared regarding presence of fQRS on electrocardiography. Additionally, multinomial logistic regression analysis was used to determine the relationship between fQRS and blood pressure pattern in prehypertensive patients. Results: According to ABPM recordings, 61 patients had normotensive blood pressure pattern (systolic blood pressure < 120 mmHg and diastolic blood pressure < 80 mmHg). Of the remaining 155 prehypertensive patients, 83 were dippers and 72 were non-dippers. Non-dipper prehypertensives had a significantly higher frequency of fQRS compared to normotensives (p = 0.048). Furthermore, multinomial logistic regression analysis revealed that fQRS is an independent predictor of non-dipping blood pressure pattern in prehypertensive patients (p = 0.017, OR: 4.071, 95% CI: 1.281-12.936). Conclusions: We found that fQRS is a predictor of non-dipping in prehypertensives. As a marker of fibrosis and higher fibrotic burden within myocardium, fQRS may be useful in identifying high-risk prehypertensive patients before the development of hypertension.